Mukowiscydoza a infekcje - Goździk, Joanna; Cofta, Szczepan (Przewodnik Lekarza/Guide for GPs Supplement, 2007)
Cystic fibrosis (CF) is a worldwide disease occurring in virtually all ethnic groups. In Caucasians it is the most common lethal hereditary disorder with autosomal recessive inheritance. Although many organs are affected in CF, lung disease is the major cause of morbidity and virtually all mortality. Ultimately, 90 to 95% of patients with CF succumb to respiratory failure brought on by chronic bacterial infection and concomitant airway inflammation. Pseudomonas aeruginosa is the dominant pathogen today in patients with CF.